Pull-out behaviour of Glass-Fibre Reinforced Polymer perforated plate connectors embedded in concrete. Part I: Experimental program - Lameiras, Rodrigo (2018)
The Glass Fibre Reinforced Polymer (GFRP) connectors studied in this work were previously proposed by the authors for connecting the outer Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC) layers of sandwich panels for prefabricated modular housing. In this building system, SFRSCC was used to totally eliminate the need for conventional reinforcement and to decrease the thickness of the panel's outer layers, with consequent reduction of the global self-weigh of the panels, while GFRP connectors aimed to significantly decrease thermal bridging effects. For a reliable design of the structural elements that make use of these connectors, the mechanical behaviour of this connection should be known and taken into account. The present paper summarizes the results obtained in an experimental research devoted to the assessment of the behaviour of GFRP-SFRSCC connection by performing pullout tests with specimens representative of the developed sandwich panel. The specimens were designed to examine the influence of the number and geometry of holes executed in the GFRP connector that assure the connection between these two materials.